Metal particle doped self-supporting carbon-based material and preparation method and application thereof

By preparing self-supporting base materials doped with metal particles in sodium ion batteries, the problems of low discharge capacity and poor circulation performance of sodium ion batteries are solved, and the effects of high discharge capacity and good circulation performance are achieved.

CN119650624APending Publication Date: 2025-03-18SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411717903.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing sodium ion batteries have low discharge capacity and poor circulation performance, making it difficult to reach a level comparable to lithium ion batteries.

Method used

By preparing self-supported carbon-based materials doped with metal particles, electrospinning technology is used to prepare carbon-based material precursors, and the load of metal element particles is significantly improved through preoxidation and calcination processes, improving the conductivity and sodium ion storage capacity of the material.

Benefits of technology

It significantly improves the discharge capacity and cycling performance of sodium ion batteries, reduces the increase in unnecessary weight in the device, and reduces the manufacturing cost. It is suitable for large-scale development and application of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650624A_ABST
    Figure CN119650624A_ABST
Patent Text Reader

Abstract

The invention provides a metal particle doped self-supporting carbon-based material as well as a preparation method and application thereof. The metal particles comprise metal elementary substance particles, and in the self-supporting carbon-based material doped with the metal particles, the loading capacity of the metal elementary substance particles is 15-55 wt%; the preparation method comprises the following steps: firstly, mixing a polymer, metal salt and a solvent, and preparing a carbon-based material precursor through electrostatic spinning; then sequentially carrying out pre-oxidation and calcination on the carbon-based material precursor; wherein the types of metal salts and the conditions of pre-oxidation and calcination are defined. According to the preparation method, by limiting the gas components in the calcination process and the temperature and time ranges in the pre-oxidation and calcination processes, the loading capacity of the metal elementary substance particles is remarkably improved, the precursor is fully carbonized to form the carbon fibers, and the prepared self-supporting carbon-based material is good in discharge capacity and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a self-supporting carbon-based material doped with metal particles, a preparation method thereof and an application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of large capacity, high power, and high voltage, and have absolute advantages in the global energy storage market. However, the uneven geographical distribution and limited reserves of lithium resources constitute a bottleneck for the continued expansion of the lithium-ion battery industry, posing a challenge to supply chain security and cost control. In this context, sodium-ion batteries, with the abundance of sodium resources on the earth and the economic cost of mining, are gradually attracting strong interest from scientific research and industry, and are seen as a potential solution to overcome the resource limitations of lithium-ion batteries.

[0003] However, the current sodium-ion batteries still have obvious shortcomings in discharge capacity and technical stability, especially in terms of cycle performance, which is difficult to reach a level comparable to lithium-ion batteries. This limits its application potential in high-demand electronic devices and leads to an urgent technical demand to improve the performance of sodium-ion batteries. Summary of the invention

[0004] The main purpose of the present invention is to provide a metal particle-doped self-supporting carbon-based material, a preparation method and application thereof, so as to solve the problems of low discharge capacity and poor cycle performance of sodium ion batteries in the prior art.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a self-supporting carbon-based material doped with metal particles is provided, wherein the metal particles include metal element particles, and in the self-supporting carbon-based material doped with metal particles, the loading amount of the metal element particles is 15-55wt%; the preparation method comprises the following steps: step S1, mixing a polymer, a metal salt and a solvent, and preparing a carbon-based material precursor by electrospinning; step S2, pre-oxidizing and calcining the carbon-based material precursor in sequence to obtain a self-supporting carbon-based material doped with metal particles; the metal salt is an iron salt, a nickel salt or a cobalt salt; the pre-oxidation temperature is 250-300°C, and the time is 1-3h; the calcination temperature is 700-1000°C, and the time is 2-8h, and the atmosphere is a mixed atmosphere of a non-reactive gas and hydrogen, and the volume ratio of the two is (80-95):(5-20), and the non-reactive gas is an inert gas or nitrogen.

[0006] The present application can significantly increase the metal element content in the metal by limiting the gas composition during calcination, the temperature and time range during pre-oxidation and calcination, so that the loading amount of metal element particles is 15-55wt%, and the precursor can be fully carbonized to form carbon fibers, so that the prepared self-supporting carbon-based material contains more free electrons, has good conductivity, can store more sodium ions, and has a wide contact area with the electrolyte, which is beneficial to improving the discharge capacity and cycle performance of the carbon-based material.

[0007] Further, the inert gas includes argon and / or helium; and / or, the polymer includes one or more of polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl alcohol, polyvinylidene fluoride and polyethylene oxide; and / or, the solvent includes one or more of NN dimethylformamide, NN dimethylacetamide and ethanol; and / or, the molar ratio of metal salt to polymer is (1-4):(4-12); and / or, the weight ratio of polymer to solvent is (1-3):20; and / or, in the self-supporting carbon-based material doped with metal particles, the loading amount of metal particles is 15-55wt%; and / or, the iron salt includes one or more of ferric nitrate, ferric chloride, and ferric sulfate; and / or, the nickel salt includes one or more of nickel nitrate, nickel chloride, and nickel sulfate; and / or, the cobalt salt includes one or more of cobalt nitrate, cobalt chloride, and cobalt acetate; and / or, the mixing method is stirring, the stirring temperature is 40-60°C, preferably 45-55°C, and the rotation speed is 100-400rpm. Under the above conditions, it is more conducive to the preparation of the membrane and can further increase the loading amount of the self-supporting carbon-based material, thereby being more conducive to improving the discharge capacity of the sodium ion battery.

[0008] Further, in step S1, the conditions for electrospinning are: voltage of 14-20 kV, preferably 16-18 kV; and / or, propulsion speed of 12-20 μL / min, preferably 14-18 μL / min; humidity of 25-40%, preferably 30-35%; temperature of 20-30° C.; and / or, time of 2-20 h. Within the above range, the pore size, length and uniformity of the nanofibers can be more effectively controlled, and the surface loading of the carbon-based material can be further increased, thereby further increasing the discharge capacity of the carbon-based material.

[0009] Furthermore, in step S2, the pre-oxidation temperature is 270-300°C, and the time is 1.5-3h; and / or the pre-oxidation heating rate is 1-20°C / min, preferably 2-5°C / min; and / or the pre-oxidation atmosphere is air or oxygen.

[0010] Further, in step S2, the calcination temperature is 800-900°C, and the time is 4-6h; and / or, the calcination heating rate is 1-10°C / min, preferably 1-5°C / min; and / or, the calcination atmosphere includes argon and hydrogen, and the volume ratio of the two is (90-95): (5-10); and / or, in the calcination atmosphere, the gas flow rate is 0.05-0.1L / min. Under the above conditions, hydrogen can more effectively prevent the metal generated by high-temperature calcination from being oxidized into metal oxides, which is more conducive to improving the purity of the prepared metal element particles, and thus more conducive to improving the cycle stability of the electrode material.

[0011] According to another aspect of the present invention, a self-supporting carbon-based material doped with metal particles is provided, which is prepared by the above-mentioned preparation method. The self-supporting carbon-based material doped with metal particles of the present application contains many free electrons, has good conductivity, can store many sodium ions, has high discharge capacity and good cycle performance when used as an electrode.

[0012] Furthermore, the specific surface area of ​​the metal particle-doped self-supporting carbon-based material is 100 to 200 m 2 / g; the size of the metal particles is 20-100nm, and the surface loading is 1.0-10.6mg·cm -2 .

[0013] According to another aspect of the present invention, a self-supporting carbon-based film doped with metal particles is provided, comprising the self-supporting carbon-based material doped with the above metal particles. The film of the present application has a high surface loading, contains many free electrons, has good conductivity, has a simple reaction mechanism with sodium ions, does not require more phase change processes, can store more sodium ions, has a wide contact area with the electrolyte, has a high discharge capacity, and has good cycle performance.

[0014] According to another aspect of the present invention, a negative electrode is provided, comprising the above-mentioned metal particle-doped self-supporting carbon-based film. The negative electrode of the present application does not require additional conductive additives, adhesives and current collectors, effectively reducing the increase of unnecessary weight in the device, thereby improving the energy density of the sodium ion battery. In addition, the negative electrode has high discharge capacity and cycle performance, low manufacturing cost, and is suitable for large-scale development and application of sodium ion batteries.

[0015] According to another aspect of the present invention, a sodium ion battery is provided, comprising the above-mentioned negative electrode. The sodium ion battery of the present invention has high discharge capacity and good cycle performance.

[0016] The present invention can significantly increase the loading amount of metal element particles by limiting the gas composition during calcination, and the temperature and time range during pre-oxidation and calcination, which is beneficial to improving the discharge capacity and cycle performance of the self-supporting carbon-based material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0018] Figure 1 The actual pictures of the flat and curved states of the self-supporting carbon-based film doped with metal Co particles according to Example 1 of the present invention are shown;

[0019] Figure 2 A cross-sectional SEM image of a self-supporting carbon-based film doped with metal Co particles according to Example 1 of the present invention is shown;

[0020] Figure 3 The XPS graph of the self-supporting carbon-based film doped with metal Co particles according to Example 1 of the present invention is shown;

[0021] Figure 4 shows a magnetization curve of a self-supporting carbon-based film doped with metal Co particles according to Example 1 of the present invention;

[0022] Figure 5 The figures show the flat and curved states of the pure carbon self-supporting film prepared in Comparative Example 1 of the present invention;

[0023] Figure 6 A comparison chart of the average loading per 100 μm of the self-supporting carbon-based films doped with metal Co particles prepared in Example 1 and Examples 8 to 12 of the present invention is shown;

[0024] Figure 7 The cycle performance diagram of the sodium ion batteries prepared in Example 1 and Examples 8 to 12 of the present invention is shown. DETAILED DESCRIPTION

[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0026] Terminology explanation:

[0027] Surface loading: the weight of active substance per unit area.

[0028] As described in the background of the present invention, there are problems in the prior art of sodium ion batteries with low discharge capacity and poor cycle performance. In order to solve the above problems, in a typical embodiment of the present invention, a method for preparing a self-supporting carbon-based material doped with metal particles is provided. The metal particles include metal element particles, and in the self-supporting carbon-based material doped with metal particles, the loading amount of the metal element particles is 15-55wt%; the preparation method comprises the following steps: step S1, mixing a polymer, a metal salt and a solvent, and preparing a carbon-based material precursor by electrostatic spinning; step S2, pre-oxidizing and calcining the carbon-based material precursor in sequence to obtain a self-supporting carbon-based material doped with metal particles; the metal salt is an iron salt, a nickel salt or a cobalt salt; the pre-oxidation temperature is 250-300°C, and the time is 1-3h; the calcination temperature is 700-1000°C, and the time is 2-8h, and the atmosphere is a mixed atmosphere of non-reactive and hydrogen, and the volume ratio of the two is (80-95): (5-20), and the non-reactive gas is an inert gas or nitrogen.

[0029] The present application first mixes a polymer, a metal salt (iron salt, nickel salt or cobalt salt) and a solvent, and performs electrostatic spinning to obtain a carbon-based material precursor, which has a large specific surface area, a high porosity and a relatively uniform fiber diameter, and is conducive to the preparation of a self-supporting carbon-based material with a three-dimensional porous structure. The carbon-based material precursor is pre-oxidized to oxidize the carbon-hydrogen bonds in the polymer, and then calcined to remove non-carbon elements such as hydrogen and oxygen to generate a carbon material. At the same time, the metal salt decomposes to obtain a self-supporting carbon-based material doped with metal particles.

[0030] The inventor has found through a large number of experiments that in the calcining atmosphere, compared with the inert gas, the mixture formed by the inert gas and hydrogen can effectively inhibit the decomposition of metal salts into metal oxides during the calcining process, so that the metal elements are fully converted into metal elements, and the loading amount of metal element particles in the self-supporting carbon-based material of the product is increased. The calcining atmosphere is specifically defined as a mixed atmosphere of inert gas and hydrogen, and the volume ratio of the two is (90-95): (5-10). Under this condition, the oxidation of metal salts to form metal oxides during the calcining process can be effectively inhibited, and the loading amount of metal element particles in the self-supporting carbon-based material doped with metal particles can be controlled to be 15-55wt%. The product has many free electrons, good conductivity, and a simple reaction mechanism with sodium ions. It does not need to go through more phase change processes, and can store more sodium ions, which can effectively improve the discharge capacity and cycle performance of the self-supporting carbon-based material doped with metal particles.

[0031] In the metal particle-doped self-supporting carbon-based material of the present application, the metal is one of Fe, Ni and Co. The above metal has a unique spin charge energy storage mechanism, which helps to maintain the integrity of the electrode structure when used in sodium ion batteries, thereby helping to improve the cycle performance of the electrode.

[0032] In addition, the pre-oxidation temperature of the present application is 250-300°C, and the time is 1-3h. Within this range, the polymer can be fully oxidized, which is beneficial to improve the heat resistance, flame retardancy and conductivity of carbon-based materials. Taking the pre-oxidation of polyacrylonitrile precursor as an example, under the pre-oxidation conditions, under appropriate tension, polyacrylonitrile undergoes a series of complex reactions such as cyclization, cross-linking, dehydrogenation, and oxidation of the molecular chain, and is converted into a pyridine ring ladder structure with good thermal stability and semiconductor resistance value, and its heat resistance, flame retardancy and conductivity are improved. If the pre-oxidation temperature becomes higher or the time becomes longer, the production efficiency is lower. If the pre-oxidation temperature becomes shorter or the time becomes shorter, it may cause insufficient oxidation of the polymer, which is not conducive to the later generation of self-supporting carbon-based materials. The calcination temperature of the present application is 700-1000°C and the time is 2-8h. Within this range, the polymer precursor can be fully converted into a carbon-based material, and the metal salt can be fully converted into a metal element. If the calcination temperature is too high or the calcination time is too long, the metal oxide content will increase, which may further reduce the discharge capacity and cycle performance of the self-supporting carbon-based material. If the calcination temperature is too low or the calcination time is too short, the carbonization of the carbon-based material may be insufficient, which is also not conducive to the improvement of the discharge capacity and cycle performance.

[0033] Moreover, the self-supporting carbon-based material of the present application presents a macroscopic three-dimensional porous structure, which can increase the contact area between the carbon-based material and the electrolyte, provide more reactive sites, promote the penetration of the electrolyte, shorten the sodium ion transmission path, and accelerate the ion diffusion process, thereby helping to improve the kinetic performance of the sodium ion battery.

[0034] In summary, the present application can significantly increase the metal content in the metal by limiting the gas composition during calcination, the temperature and time range during pre-oxidation and calcination, so that the loading amount of metal particles in the self-supporting carbon-based material doped with metal particles is 15-55wt%, and the precursor can be fully carbonized to form carbon fibers, so that the prepared self-supporting carbon-based material contains more free electrons, has good conductivity, can store more sodium ions, and has a wide contact area with the electrolyte, which is beneficial to improve the discharge capacity and cycle performance of the carbon-based material.

[0035] In order to facilitate practical preparation and further increase the loading amount of the self-supporting carbon-based material, thereby being more conducive to improving the discharge capacity of the sodium ion battery, in a preferred embodiment, the inert gas includes argon and / or helium; and / or the polymer includes one or more of polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl alcohol, polyvinylidene fluoride and polyethylene oxide; and / or the solvent includes one or more of NN dimethylformamide, NN dimethylacetamide and ethanol; and / or the molar ratio of the metal salt to the polymer is (1-4): (4-12); and / or the weight ratio of the polymer to the solvent is (1-3): 20; and / or, in the self-supporting carbon-based material doped with metal particles, the loading amount of the metal particles is 15-55wt%.

[0036] In order to further improve the compatibility and uniformity of each raw material, in a preferred embodiment, the iron salt includes one or more of iron nitrate, iron chloride, and iron sulfate; and / or the nickel salt includes one or more of nickel nitrate, nickel chloride, and nickel sulfate; and / or the cobalt salt includes one or more of cobalt nitrate, cobalt chloride, and cobalt acetate. In a preferred embodiment, the mixing method is stirring, the stirring temperature is 40 to 60°C, preferably 45 to 55°C, and the rotation speed is 100 to 400rpm.

[0037] In a preferred embodiment, in step S1, the conditions for electrospinning are: voltage of 14-20 kV, preferably 16-18 kV; and / or, propulsion speed of 12-20 μL / min, preferably 14-18 μL / min; and / or, humidity of 25-40% RH, preferably 30-35% RH; temperature of 20-30° C.; time of 2-20 h. By adjusting the voltage, polymer solution propulsion speed, ambient humidity, temperature and time within the above range, the pore size, length and uniformity of the nanofibers can be more effectively controlled, and the surface loading of the carbon-based material can be further increased, thereby further increasing the discharge capacity of the carbon-based material.

[0038] In a preferred embodiment, in step S2, the pre-oxidation temperature is 270-300°C, and the time is 1.5-3h; and / or, the pre-oxidation heating rate is 1-20°C / min, preferably 2-5°C / min; and / or, the pre-oxidation atmosphere is air or oxygen. In a preferred embodiment, in step S2, the calcination temperature is 800-900°C, and the time is 4-6h; the calcination heating rate is 1-10°C / min, preferably 1-5°C / min; the calcination atmosphere includes argon and hydrogen, and the volume ratio of the two is (90-95): (5-10); and / or, in the calcination atmosphere, the gas flow rate is 0.05-0.1L / min. Under the above conditions, hydrogen can more effectively prevent the metal generated by high-temperature calcination from being oxidized to metal oxides, which is more conducive to increasing the loading amount of the prepared metal element particles, and thus more conducive to improving the cycle stability of the electrode material.

[0039] In order to make each raw material react more fully, the present application preferably sets different process conditions for different doping metals. Specifically, in a preferred embodiment, when the metal is Fe, the molar ratio of the iron salt to the polymer is (2-4): (24-36), the weight ratio of the polymer to the solvent is (2-4): 20, the iron salt is anhydrous ferric chloride, and the polymer is polyacrylonitrile; and / or, the pre-oxidation temperature is 270-290°C, the time is 2-3h, and the atmosphere is air; and / or, the calcination The temperature is 800-900°C, the time is 4-6h, the atmosphere is an argon-hydrogen mixture, and the volume ratio of argon to hydrogen is (90-95):(5-10); and / or, in the self-supporting carbon-based material doped with metal particles, the loading amount of metal element particles is 30-50wt%; when the metal is Ni, the molar ratio of nickel salt to polymer is (3-6):(12-24), the weight ratio of polymer to solvent is (1-2):20, the nickel salt is nickel chloride hexahydrate, and the polymer is polyacrylonitrile; and / or, The pre-oxidation temperature is 270-290°C, the time is 2-3h, and the atmosphere is air; and / or, the calcination temperature is 800-850°C, the time is 5-6h, the atmosphere is an argon-hydrogen mixture, and the volume ratio of argon to hydrogen is (90-95):(5-10); and / or, in the self-supporting carbon-based material doped with metal particles, the loading amount of metal element particles is 35-55wt%; when the metal is Co, the molar ratio of cobalt salt to polymer is (1-4):(12-24), and the ratio of polymer to solvent is (1-4):(12-24). The weight ratio is (1-2):20, the cobalt salt is cobalt nitrate hexahydrate, and the polymer is polyacrylonitrile; and / or, the pre-oxidation temperature is 270-290°C, the time is 1.5-2.5h, and the atmosphere is air; and / or, the calcination temperature is 800-850°C, the time is 5-6h, the atmosphere is an argon-hydrogen mixture, and the volume ratio of argon to hydrogen is (90-95):(5-10); and / or, in the self-supporting carbon-based material doped with metal particles, the loading amount of metal element particles is 15-45wt%.

[0040] In another typical embodiment of the present invention, a self-supporting carbon-based material doped with metal particles is provided, which is prepared by the above preparation method. The self-supporting carbon-based material doped with metal particles of the present application contains more free electrons, has good conductivity, and can store more sodium ions.

[0041] Specifically, in a preferred embodiment, the specific surface area of ​​the metal particle-doped self-supporting carbon-based material is 100 to 200 m 2 / g; the size of the metal particles is 20-100nm, and the surface loading is 1.0-10.6mg·cm -2 .

[0042] In another typical embodiment of the present invention, a self-supporting carbon-based film doped with metal particles is also provided, including the self-supporting carbon-based material doped with the above-mentioned metal particles. The film surface loading of the present application is high, contains many free electrons, has good conductivity, has a simple reaction mechanism with sodium ions, does not need to go through more phase change processes, can store more sodium ions, has a wide contact area with the electrolyte, has a high discharge capacity, and has good cycle performance. In a preferred embodiment, the thickness of the carbon-based film doped with metal particles is 100 to 1000 μm.

[0043] In a preferred embodiment, the relationship between the electrospinning time (x, in h) and the thickness of the metal particle-doped self-supporting carbon-based film (y, in μm) is: y=Kx, K=48-52, in μm / h. The present application specifically defines the relationship between the electrospinning time (x, in h) and the thickness of the metal particle-doped carbon-based film, so that the film thickness can be more effectively and accurately controlled, which is more conducive to improving the preparation efficiency of high-load electrodes.

[0044] In another typical embodiment of the present invention, a negative electrode is also provided, comprising the self-supporting carbon-based film doped with the above-mentioned metal particles. The negative electrode of the present application does not require additional conductive additives, adhesives and current collectors, effectively reducing the increase of unnecessary weight in the device, thereby improving the energy density of the sodium ion battery. In addition, the negative electrode has high discharge capacity and cycle performance, low manufacturing cost, and is suitable for large-scale development and application of sodium ion batteries.

[0045] In another typical embodiment of the present invention, a sodium ion battery is provided, comprising the above-mentioned negative electrode. The sodium ion battery has high discharge capacity and good cycle performance.

[0046] Typically but not limiting, the calcination temperature is 700°C, 800°C, 900°C, 1000°C, the time is 2h, 4h, 6h, 8h, and the volume ratio of inert gas to hydrogen in the atmosphere is 80:20, 85:15, 90:10, 95:5.

[0047] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0048] Example 1

[0049] Step S1, weighing raw materials according to the ratio of metal salt to polymer of 1:4 and polymer to solvent of 1:10, adding 2.0 g of polyacrylonitrile powder into 20 g of N-N-dimethylformamide solution and sealing, stirring continuously at 25°C for 24 h to obtain a uniform transparent solution A, and then adding 2.93 g of Co(NO 3 ) 2 6H2 O crystal powder was added to the transparent solution A and stirred at room temperature for 1 h until completely dissolved to obtain a purple mixed solution B. The obtained purple mixed solution B was transferred to a syringe and spun into a film using a TTE-1 electrospinning machine. The distance from the needle to the receiving axis was 15 cm, the spinning time was about 10 h, and a lavender self-supporting film precursor was obtained. The spinning conditions were: voltage 18 kV, propulsion speed 16 μL / min, humidity 35% RH, temperature 25 ° C.

[0050] Step S2, heat to 280°C in an air atmosphere at a pre-oxidation heating rate of 5°C / min, and pre-oxidize the obtained thin film precursor for 2 hours. The pre-oxidized thin film material is placed in a high-temperature tube furnace for calcination. The calcination atmosphere is a mixture of argon and hydrogen with a volume ratio of 9:1. The gas flow rate in the calcination atmosphere is 0.05L / min. The temperature is increased to 800°C at a heating rate of 5°C / min and maintained for 6 hours to obtain a self-supporting carbon-based film doped with metal Co particles. By measurement, the thickness of the self-supporting carbon-based film doped with metal Co particles is about 500μm, and the specific surface area is 100.9m 2 ·g -1 The particle size of the metal single substance Co particles is 25 to 50 nm.

[0051] The flat and curved states of the self-supporting carbon-based film doped with metal Co particles are shown in the following figure. Figure 1 , showing good mechanical flexibility, meeting the preparation requirements of flexible sodium-ion batteries. The cross-sectional SEM image of the self-supporting carbon-based film doped with metal Co particles is shown in Figure 2 The thickness of the fiber membrane is uniform, and it can be clearly seen that the film is composed of layers of staggered nanofibers. The abundant pores between the nanofibers are conducive to the infiltration of the electrolyte and can provide abundant active sites for electrochemical reactions, which is beneficial to improving its electrochemical performance in sodium ion batteries.

[0052] The XPS images of the free-standing carbon-based films doped with metal Co particles are shown in Figure 3 The high-resolution spectrum of Co 2p at 778eV corresponds to Co 2p3 / 2, and the peak at 775eV belongs to its satellite peak. According to the fitting analysis, in addition to the 0-valent metal Co (778eV), there is also a small amount of +2-valent Co (780.1eV). The small amount of cobalt oxide is mainly due to the active chemical properties of metal Co, which is easier to oxidize in the air.

[0053] The content of metal Co was calculated by saturation magnetization test. The magnetization curve of the self-supporting carbon-based film doped with metal Co particles is shown in Figure 4 .according to Figure 4 It can be seen that the magnetization intensity of the self-supporting carbon-based film doped with metal Co particles is 35.1emu g-1 , it has shown obvious ferromagnetism. According to the saturation magnetization intensity of metal Co single substance is 136emu / g, it can be calculated that the metal Co content in the self-supporting film material is 35.1 / 136=25.8wt%.

[0054] Example 2

[0055] Step S1, weigh the raw materials according to the ratio of the molar ratio of the metal salt to the polymer being 1:4 and the weight ratio of the polymer to the solvent being 1:10, add 2.0g of polyacrylonitrile powder to 20g of N-N dimethylformamide solution and seal, stir continuously at room temperature for 24h to obtain a uniform transparent solution A, then add 1.62g of anhydrous ferric chloride crystal powder to the transparent solution A and stir at room temperature for 1h until completely dissolved to obtain a purple mixed solution B. The obtained purple mixed solution B is transferred to a syringe and spun into a film using a TTE-1 type electrospinning machine, the spinning time is about 9h, and a light yellow self-supporting film precursor is obtained, and the spinning conditions are: voltage 16kV, propulsion speed 18μL / min, humidity 30%RH, temperature 25°C.

[0056] Step S2, heating to 260°C in air atmosphere at a pre-oxidation heating rate of 5°C / min, pre-oxidation treatment of the obtained film precursor for 2 hours. The pre-oxidation treated film material is placed in a high-temperature tube furnace for calcination, the calcination atmosphere is a mixture of argon and hydrogen, the volume ratio of the two is 9:1, the gas flow rate in the calcination atmosphere is 0.05L / min, and the temperature is increased to 900°C at a heating rate of 5°C / min, and maintained for 4 hours to obtain a self-supporting carbon-based film doped with metal Fe particles; by measurement, the thickness of the self-supporting carbon-based film doped with metal Fe particles is about 500μm.

[0057] The analysis shows that the specific surface area of ​​the self-supporting carbon-based film doped with metal Fe particles is 107.6 m 2 ·g -1 The particle size of the metal Fe particles is 30-60 nm, and the metal Fe content in the self-supporting film material is 51.7 / 219=23.6wt%.

[0058] Example 3

[0059] Step S1, weighing raw materials according to the ratio of metal salt to polymer of 1:4 and polymer to solvent of 1:10, adding 2.0 g of polyacrylonitrile powder into 20 g of N-N-dimethylformamide solution and sealing, stirring continuously at room temperature for 24 h to obtain a uniform transparent solution A, and then adding 2.90 g of Ni(NO 3 ) 2 6H 2O crystal powder was added to the transparent solution A and stirred at room temperature for 1 h until completely dissolved to obtain a purple mixed solution B. The light green mixed solution B was transferred to a syringe and spun into a film using a TTE-1 electrospinning machine. The spinning time was about 11.5 h to obtain a light yellow self-supporting film precursor. The spinning conditions were: voltage 18 kV, propulsion speed 14 μL / min, humidity 35% RH, temperature 25 °C.

[0060] Step S2, heating to 300°C in air atmosphere at a pre-oxidation heating rate of 5°C / min, and pre-oxidizing the obtained thin film precursor for 2 hours. The pre-oxidized thin film material is placed in a high-temperature tube furnace for calcination, the calcination atmosphere is a mixture of argon and hydrogen, the volume ratio of the two is 9:1, the gas flow rate in the calcination atmosphere is 0.05L / min, and the temperature is increased to 900°C at a heating rate of 5°C / min, and maintained for 6 hours to obtain a self-supporting film doped with metal Ni particles. The thickness of the self-supporting film doped with metal Ni particles is about 500μm as measured by a micrometer caliper.

[0061] The analysis shows that the specific surface area of ​​the self-supporting film doped with metal Ni particles is 103.9 m 2 ·g -1 The particle size of the metal Fe particles is 20-50 nm, and the metal Ni content is 13.2 / 54.4=24.3wt%.

[0062] Example 4

[0063] The only difference from Example 1 is:

[0064] The calcination atmosphere is a mixture of argon and hydrogen, and the volume ratio of argon to hydrogen is 80:20.

[0065] The analysis shows that the specific surface area of ​​the self-supporting film doped with metal Co particles is 102.4 m 2 ·g -1 The particle size of the metal single substance Co particles is 20 to 45 nm, and the metal Co content is 26.7 wt%.

[0066] Example 5

[0067] The only difference from Example 1 is:

[0068] The calcination atmosphere is a mixture of argon and hydrogen, and the volume ratio of argon to hydrogen is 95:5.

[0069] The analysis shows that the specific surface area of ​​the self-supporting film doped with metal Co particles is 100.2 m 2 ·g -1 The particle size of the metal single substance Co particles is 20 to 50 nm, and the metal Co content is 25.1 wt%.

[0070] Example 6

[0071] The only difference from Example 1 is:

[0072] The obtained thin film precursor was pre-oxidized for 3 h by heating to 270 °C at a heating rate of 2 °C / min;

[0073] The temperature was raised to 900°C at a heating rate of 5°C / min and maintained for 4 hours for calcination. Analysis showed that the specific surface area of ​​the self-supporting film doped with metal Co particles was 101.3 m 2 ·g -1 The particle size of the metal single substance Co particles is 20 to 45 nm, and the metal Co content is 26.2 wt%.

[0074] Example 7

[0075] The only difference from Example 1 is:

[0076] The temperature was raised to 300°C at a heating rate of 5°C / min, and the obtained thin film precursor was pre-oxidized for 1.5h;

[0077] The temperature was raised to 800°C at a heating rate of 1°C / min and maintained for 6 hours for calcination.

[0078] The analysis shows that the specific surface area of ​​the self-supporting film doped with metal Co particles is 100.6 m 2 ·g -1 The particle size of the metal single substance Co particles is 20 to 45 nm, and the metal Co content is 26 wt%.

[0079] Example 8

[0080] The only difference from Example 1 is:

[0081] The spinning time was 2 h. The thickness of the prepared metal Co particle-doped self-supporting carbon-based film was about 100 μm.

[0082] The analysis shows that the specific surface area of ​​the self-supporting film doped with metal Co particles is 101.3 m 2 ·g -1 The particle size of the metal single substance Co particles is 20 to 45 nm, and the metal Co content is 25.8 wt%.

[0083] Example 9

[0084] The only difference from Example 1 is:

[0085] The spinning time is 4 hours. The thickness of the prepared metal Co particle doped self-supporting carbon-based film is about 200 μm.

[0086] The analysis shows that the specific surface area of ​​the self-supporting film doped with metal Co particles is 101.5 m 2 ·g -1 The particle size of the metal single substance Co particles is 20 to 45 nm, and the metal Co content is 25.8 wt%.

[0087] Example 10

[0088] The only difference from Example 1 is:

[0089] The spinning time was 6 hours. The thickness of the prepared metal Co particle doped self-supporting carbon-based film was about 300 μm.

[0090] The analysis shows that the specific surface area of ​​the self-supporting film doped with metal Co particles is 100.8 m 2 ·g -1 The particle size of the metal single substance Co particles is 20 to 45 nm, and the metal Co content is 26 wt%.

[0091] Embodiment 11

[0092] The only difference from Example 1 is:

[0093] The spinning time was 8 hours. The thickness of the prepared metal Co particle doped self-supporting carbon-based film was about 400 μm.

[0094] The analysis shows that the specific surface area of ​​the self-supporting film doped with metal Co particles is 101.0 m 2 ·g -1 The particle size of the metal single substance Co particles is 20 to 45 nm, and the metal Co content is 26 wt%.

[0095] Example 12

[0096] The only difference from Example 1 is:

[0097] The spinning time was 12 h. The thickness of the prepared metal Co particle-doped self-supporting carbon-based film was about 600 μm.

[0098] The analysis shows that the specific surface area of ​​the self-supporting film doped with metal Co particles is 100.3 m 2 ·g -1 The particle size of the metal single substance Co particles is 20 to 45 nm, and the metal Co content is 26 wt%.

[0099] Comparative Example 1

[0100] The only difference from Example 1 is:

[0101] In step S1, without adding a metal compound raw material, 2.0 g of polyacrylonitrile is dissolved in 20 g of NN dimethylformamide solution to obtain a spinning solution, and a pure carbon self-supporting film is obtained by the same preparation method.

[0102] See the actual pictures of the flat and bent states of the pure carbon self-supporting film. Figure 5 As can be seen from the figure, part of the fiber membrane fell off during the bending process, showing poor mechanical flexibility, which is difficult to meet the preparation requirements of flexible sodium-ion batteries; the thickness of the prepared metal Co particle-doped self-supporting carbon-based film is about 500μm.

[0103] The analysis shows that the pure carbon self-supporting film has a specific surface area of ​​5.2 m 2 ·g -1 .

[0104] Comparative Example 2

[0105] The only difference from Example 1 is:

[0106] The calcination atmosphere was argon and did not contain hydrogen.

[0107] The analysis shows that the specific surface area of ​​the self-supporting film is 96.7m 2 ·g -1 The particle size of the metal single substance Co particles is 40-100 nm, and the metal Co content is 10.4 wt%. Since there is no introduction of hydrogen to reduce the oxidized metal particles, a large amount of cobalt oxide is contained in the film. Compared with Example 1, the cycle stability of Comparative Example 2 is poor.

[0108] Comparison of the average loading per 100 μm of the self-supporting carbon-based films doped with metal Co particles prepared in Example 1 and Examples 8 to 12 Figure 6 It can be seen that the fluctuation trend of the loading under different thicknesses is stable, showing good uniformity and stability, which can meet the controllability requirements of electrode preparation with different loading requirements.

[0109] A sodium ion battery was assembled in an argon-protected glove box with an anhydrous and oxygen-free (water and oxygen content ≤ 0.01 ppm) CR-2032 stainless steel button battery case. The positive electrode case, the carbon-based film prepared in the above embodiments and comparative examples, the diaphragm, the electrolyte (1.0 M NaClO 4 EC:DMC=1:1Vol%+5.0%FEC), a sodium sheet, a gasket, and a negative electrode shell are assembled in sequence, and the device is sealed at a pressure not higher than 0.5MPa to obtain a sodium ion battery.

[0110] The cycle performance diagrams of the sodium ion batteries prepared in Example 1 and Examples 8 to 12 are shown in Figure 7With the continuous increase of film thickness, that is, the increase of film surface loading, the discharge area capacity shows a cycling trend of increasing continuously, and all of them can show good cycling stability.

[0111] The application performance test results of the sodium ion batteries prepared in the above embodiments and comparative examples are shown in Table 1.

[0112] Test method:

[0113] Size of metal particles: refer to the high-resolution transmission electron microscope detection method of GB / Z 21738-2008, use nano measure software to perform statistical analysis on the size, length and other dimensions of metal particles to obtain the particle size distribution data of metal particles;

[0114] Determination of metal content in materials: The prepared MXene-based composite materials were subjected to an initial hysteresis loop test using the comprehensive physical property measurement system (PPMS) of Quantum Design, USA. The test conditions were room temperature 300K and a constant electric field of 3T. The ratio of the measured value to the magnetic value of the pure transition metal material was the metal content in the composite material.

[0115] Discharge performance: Using the NEWARE BTS-5V battery charge and discharge test system, at a constant temperature of 25°C, the assembled sodium ion battery was tested at 0.0~3.0V (vs.Na / Na + ) voltage range, 5.4uA / cm 2 100 cycles of charge and discharge test were carried out at a current density of .

[0116] Table 1

[0117]

[0118] From the above, it can be seen that compared with the comparative example, the embodiment of the method of the present invention can significantly increase the content of metal element particles in the metal particles by limiting the gas composition during calcination, and the temperature and time range during pre-oxidation and calcination, which is beneficial to improving the discharge capacity and cycle performance of self-supporting carbon-based materials.

[0119] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the discharge capacity and cycle performance of the sodium ion battery are better.

[0120] As can be seen from the above, it can be seen from Table 1 that the high-loading self-supporting carbon-based films doped with transition metal Co, Fe, and Ni particles can all exhibit higher first-cycle discharge capacity and good cycle stability; by comparing the performance of Example 1 with that of Comparative Example 1, it can be seen that the thin film electrode doped with transition metal particles has significantly improved its first-cycle discharge capacity and cycle stability performance due to the introduction of the spin space charge energy storage mechanism, and the flexibility, specific surface area and other physical characterization properties of the film are significantly improved.

[0121] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a self-supporting carbon-based material doped with metal particles, characterized in that: The metal particles include metal element particles, and in the self-supporting carbon-based material doped with the metal particles, the loading amount of the metal element particles is 15 to 55 wt %; The preparation method comprises the following steps: Step S1, mixing a polymer, a metal salt and a solvent, and preparing a carbon-based material precursor by electrospinning; Step S2, pre-oxidizing and calcining the carbon-based material precursor in sequence to obtain the metal particle-doped self-supporting carbon-based material; The metal salt is an iron salt, a nickel salt or a cobalt salt; The pre-oxidation temperature is 250-300°C and the time is 1-3h; The calcination temperature is 700-1000° C., the time is 2-8 hours, the atmosphere is a mixed atmosphere of non-reactive gas and hydrogen, the volume ratio of the two is (80-95):(5-20), and the non-reactive gas is an inert gas or nitrogen.

2. The preparation method according to claim 1, characterized in that: The inert gas comprises argon and / or helium; and / or, The polymer includes one or more of polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl alcohol, polyvinylidene fluoride and polyethylene oxide; and / or, The solvent includes one or more of NN dimethylformamide, NN dimethylacetamide and ethanol; and / or, The molar ratio of the metal salt to the polymer is (1-4): (4-12); and / or, The weight ratio of the polymer to the solvent is (1-3):20; and / or, The iron salt includes one or more of ferric nitrate, ferric chloride and ferric sulfate; and / or, The nickel salt includes one or more of nickel nitrate, nickel chloride, and nickel sulfate; and / or, The cobalt salt includes one or more of cobalt nitrate, cobalt chloride, and cobalt acetate; and / or, The mixing method is stirring, the stirring temperature is 40 to 60° C., preferably 45 to 55° C., and the rotation speed is 100 to 400 rpm.

3. The preparation method according to claim 1 or 2, characterized in that: In step S1, the electrospinning conditions are: The voltage is 14 to 20 kV, preferably 16 to 18 kV; and / or, The propulsion speed is 12 to 20 μL / min, preferably 14 to 18 μL / min; and / or, The humidity is 25-40%, preferably 30-35%, the temperature is 20-30°C, and the time is 2-20 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that In the step S2, The pre-oxidation temperature is 270-300° C. and the time is 1.5-3 hours; and / or, The heating rate of the pre-oxidation is 1 to 20°C / min, preferably 2 to 5°C / min; and / or, The pre-oxidation atmosphere is air or oxygen.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step S2, The calcination temperature is 800-900°C and the calcination time is 4-6 hours; and / or, The heating rate of the calcination is 1 to 10°C / min, preferably 1 to 5°C / min; and / or, The calcining atmosphere comprises argon and hydrogen in a volume ratio of (90-95):(5-10); and / or, In the calcination atmosphere, the gas flow rate is 0.05 to 0.1 L / min.

6. A self-supporting carbon-based material doped with metal particles, characterized in that: The preparation method is described in any one of claims 1 to 5.

7. The metal particle-doped self-supporting carbon-based material according to claim 6, characterized in that: The specific surface area of ​​the metal particle-doped self-supporting carbon-based material is 100 to 200 m 2 / g; the size of the metal particles is 20-100nm, and the surface loading is 1.0-10.6mg·cm -2 .

8. A self-supporting carbon-based film doped with metal particles, characterized in that: A self-supporting carbon-based material doped with metal particles as claimed in claim 6 or 7.

9. A negative electrode, characterized in that A self-supporting carbon-based film doped with metal particles as claimed in claim 8.

10. A sodium ion battery, characterized in that: Comprising the negative electrode as claimed in claim 9.

Citation Information

Cited By

  • Carbon-based self-supporting electrode material, preparation method and application

    CN121123223A